Psychophysiological (Individual) Prerequisites of The Teacher's Activity - Boboev Abror Hotamovich (Genius Journals, 2021)
In this work, we have considered the topic of pedagogical abilities and personal qualities of a teacher. We examined the requirements of society for the personality of the teacher, his subjective properties, the teacher's abilities and their relationship with individual characteristics, the general and professional-pedagogical qualities of the teacher's personality. We have studied the pedagogical abilities and personal qualities of the teacher, the structure of the subjective properties of the teacher, as well as the correspondence of the personal qualities (individual, congenital and actually personal, acquired during life) of a person of pedagogical activity.
Keywords: Personal Qualities; Subjective Properties; Congenital And Actually Personal; Correspondence